Multigene Expression Assay and Benefit of Radiotherapy After Breast Conservation in Ductal Carcinoma in Situ - Rakovitch, Eileen (J Natl Cancer Inst, 2016)
Background: Most women with ductal carcinoma in situ (DCIS) will receive breast-conserving surgery (BCS) and radiation (RT). RT can be omitted for women at low risk of local recurrence (LR). The Oncotype DX DCIS score (DS) predicts LR risk after BCS alone. This study assesses the impact of RT and DS on LR risk. Methods: Population-based cohort analysis of individuals with DCIS treated by BCS ± RT from 1994–2003. Treatment and outcomes were determined by linkage and chart review. We used a propensity score–adjusted multivariable model to examine associations between DS and LR and evaluate the impact of RT. All statistical tests were two-sided. Results: The cohort includes 571 individuals treated by BCS alone, 689 cases treated with BCS + RT. Median follow-up was 9.4 years. On multivariable analysis, factors associated with LR include RT, age at diagnosis, tumor size, and multifocality. Adjusting for these factors, the DS risk group was statistically significantly associated with LR risk (hazard ratio high/intermediate = 1.75, 95% confidence interval = 1.28 to 2.41, P < .001). Women with a low-risk DS treated by BCS alone had an LR risk of 10.6% at 10 years and a small benefit from RT, while those with a high DS had a higher risk of LR (25.4%) after BCS alone and greater benefit from RT. A subgroup of patients with favorable clinicopathological features had a high-risk DS; these patients had a higher than expected risk of LR after BCS alone and a greater benefit with RT. Conclusions: The DS molecular assay improves risk stratification and estimates of RT benefit in individuals with DCIS treated with breast-conserving therapy.